SOUTHTRAC-GW: An Airborne Field Campaign to Explore Gravity Wave Dynamics at the World’s Strongest Hotspot - Rapp, Markus; Kaifler, Bernd; Dörnbrack, Andreas; Gisinger, Sonja; Mixa, Tyler; Reichert, Robert; Kaifler, Natalie; Knobloch, Stefanie; Eckert, Ramona; Wildmann, Norman; Giez, Andreas; Krasauskas, Lukas; et al. (Bulletin of the American Meteorological Society, 2020)
The southern part of South America and the Antarctic peninsula are known as the world’s strongest hotspot region of stratospheric gravity wave (GW) activity. Large tropospheric winds are deflected by the Andes and the Antarctic Peninsula and excite GWs that might propagate into the upper mesosphere. Satellite observations show large stratospheric GW activity above the mountains, the Drake Passage, and in a belt centered along 60°S. This scientifically highly interesting region for studying GW dynamics was the focus of the Southern Hemisphere Transport, Dynamics, and Chemistry–Gravity Waves (SOUTHTRAC-GW) mission. The German High Altitude and Long Range Research Aircraft (HALO) was deployed to Rio Grande at the southern tip of Argentina in September 2019.